Finite Element Analysis for The Response of URM Walls Supporting RC Slab - Rafid Ahmed, Ammar; H. Al-Zuhairi, Alaa (International Journal of Engineering and Technology, 2018)
The aim for this research is to investigate the effect of inclusion of crack incidence into the 2D numerical model of the masonry units and bonding mortar on the behavior of unreinforced masonry walls supporting a loaded reinforced concrete slab. The finite element method was implemented for the modeling and analysis of unreinforced masonry walls. In this paper, ABAQUS, FE software with implicit solver was used to model and analyze unreinforced masonry walls which are subjected to a vertical load. Detailed Micro Modeling technique was used to model the masonry units, mortar and unit-mortar interface separately. It was found that considering potential pure tensional cracks located vertically in the middle of the mortar and units shows an increase in masonry strength of about 10% than the strength calculated using the procedure recommended by the Masonry Society Joint Committee in the building code.Â Â